Early Marriage Among Sasak Boys in Rural North Lombok - Lisa Colquhoun; Pamela Nilan (Jurnal Studi Pemuda, 2020)
Child marriage remains a pattern in parts of Indonesia despite recent legislative attempts to ban the practice. Previous studies of the phenomenon have primarily concerned girls. Against that research trend, this article seeks to shed light on early marriage among Sasak boys in rural north Lombok, West Nusa Tenggara. It draws on the narratives of six young Sasak men who were married during their mid-teens. Our analysis focusses on the sustained and potent influence of traditional cultural and religious practices, gendered norms of romance and sexual conduct, and normalised early youth transitions in a context of inter-generational poverty.